Pengaruh Risiko Kredit, Risiko Likuiditas dan Risiko Operasional Terhadap Profitabilitas PT Bank Mega Tbk Periode 2014-2021 - Samuel Fredi Siagian Siagian; Rodiana Listiawati (Account : Jurnal Akuntansi, Keuangan dan Perbankan, 2022)
Banks are financial institutions that function as financial intermediaries between parties who have excess funds and parties who lack funds. In carrying out its role in facilitating payment traffic and services to the community, improving credit services as the bank's main service product will affect the bank's success in achieving profit. Profitability is influenced by several factors, including Credit Risk (NPL), Liquidity Risk (LDR), and Operational Risk (BOPO). This study aims to determine the effect of NPL, LDR and BOPO on Profitability at PT Bank Mega Tbk in 2014-2021 Period. The data used in this study is the Quarterly Financial Statements of Bank Mega for the 2014-2021 period. The type of data used is secondary data obtained from financial reports published through the official website of Bank Mega. The analytical method used is multiple linear regression with a significance level of 5%. The results of this study indicate that NPL and LDR partially have no significant effect on profitability, while BOPO partially has a negative effect on profitability. Simultaneously, Credit Risk (NPL), Liquidity Risk (LDR), and Operational Risk (BOPO) have a significant effect on profitability by 94%, and other factors outside of this study influence the remaining 6%.